2018
DOI: 10.1007/s00592-018-1124-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment response to liraglutide in type 2 diabetes in a real-world setting

Abstract: AimsThere is an unmet need among healthcare providers to identify subgroups of patients with type 2 diabetes who are most likely to respond to treatment.MethodsData were taken from electronic medical records of participants of an observational, retrospective study in Italy. We used logistic regression models to assess the odds of achieving glycated haemoglobin (HbA1c) reduction ≥ 1.0% point after 12-month treatment with liraglutide (primary endpoint), according to various patient-related factors. RECursive Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…This would argue for an independent assessment of the reduction in weight and glycemia in the decision to continue GLP-1RAs therapy, which is further supported by the results of the multivariate analysis. The most important predictor of the reduction of ≥1% in HbA1c was a high baseline value, as previously reported by both observational studies and RCTs [45,46,47,48,49], and the odds were independent of the baseline BMI. Besides, a high initial BMI is the most important determinant of a weight reduction of ≥3%, which is also in line with other studies [50], and the likelihood was in turn independent of the baseline HbA1c.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This would argue for an independent assessment of the reduction in weight and glycemia in the decision to continue GLP-1RAs therapy, which is further supported by the results of the multivariate analysis. The most important predictor of the reduction of ≥1% in HbA1c was a high baseline value, as previously reported by both observational studies and RCTs [45,46,47,48,49], and the odds were independent of the baseline BMI. Besides, a high initial BMI is the most important determinant of a weight reduction of ≥3%, which is also in line with other studies [50], and the likelihood was in turn independent of the baseline HbA1c.…”
Section: Discussionsupporting
confidence: 75%
“…The independent likelihood of achieving a beneficial change in glycemia and weight loss has been previously observed [26,27,45,49,50,51], and the weak or absent correlation between the magnitude in HbA1c and weight loss is not new [26,27,34,50,51]. The reasons for this could relate to the pleiotropic actions and distinct physiopathological pathways triggering each of the effects [43], and the patient-to-patient variability in the degree of improvement in glycemia and weight could be partially attributed to an underlying differential biological response.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Baseline BMI as a predictor of the efficacy of glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA) treatment in lowering HbA1c is not fully characterized . In real‐world settings, analyses suggest that baseline BMI does not modify the efficacy of liraglutide treatment in patients with type 2 diabetes . In these studies, mean baseline BMI was reported to be 35.6 and 37.1 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1 In real-world settings, analyses suggest that baseline BMI does not modify the efficacy of liraglutide treatment in patients with type 2 diabetes. 2,3 In these studies, mean baseline BMI was reported to be 35. 6 and 37.1 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%